2020
DOI: 10.1039/d0ra00673d
|View full text |Cite
|
Sign up to set email alerts
|

Convergent access to bis-1,2,4-triazinyl-2,2′-bipyridines (BTBPs) and 2,2′-bipyridines via a Pd-catalyzed Ullman-type reaction

Abstract: Access to functionalized BTBP complexants through a reductive coupling strategy decreases linearity of common synthetic strategies towards these relevant materials for separations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The versatility of the hypervalent iodine Dess-Martin oxidant 17 applied towards ketone synthesis piqued our inter- Organic & Biomolecular Chemistry Paper est, but ultimately resulted in no conversion of 6 to 2. Metalhalogen exchange was a logical forward step given prior success in the cases of Negishi 18 and Ullman-type 19 cross-couplings with 4 described in earlier work from our lab. In both of the preceding cases, mechanistic theory substantiates the need for transmetalation as a requisite step for a successful crosscoupling outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The versatility of the hypervalent iodine Dess-Martin oxidant 17 applied towards ketone synthesis piqued our inter- Organic & Biomolecular Chemistry Paper est, but ultimately resulted in no conversion of 6 to 2. Metalhalogen exchange was a logical forward step given prior success in the cases of Negishi 18 and Ullman-type 19 cross-couplings with 4 described in earlier work from our lab. In both of the preceding cases, mechanistic theory substantiates the need for transmetalation as a requisite step for a successful crosscoupling outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Other applications of BTPs in An separations have also been disclosed . Complexants incorporating different Lewis basic cores, including 2,2′-bipyridine-2,6-bis-carbonitrile or 1,10-phenanthroline-2,6-biscarbonitrile have been prepared and evaluated in separation assays with congruent, and sometimes improved performance over traditionally symmetric BTPs . Complexants for hydrophilic separations discretely, or in concert with other separation strategies, as well as resin-bound applications have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,6 Nitrogen donors are preferred over sulfur, because the structures can be completely incinerated to environmentally benign gas phase products post complexation, whereas extant S donor extractants can leave a solid residue, making the products of the incineration harder and more difficult to store and, ultimately, to recover. 1,2 There are a large number of computational and experimental studies on bis-1,2,4-triazinylpyridines (BTP, Figure 1a), 7,8 BTP-like compounds such as bis(1,2,4-triazinyl)bipyridines (BTBP, Figure 1b), 9 as well as bis(1,2,4-triazinyl)-1,10phenanthrolines, 10 and their derivatives. 11−42 Computational studies of related ligands containing C, H, O, and N have also been reported, 43−46 although experimental data are largely lacking for these systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are a large number of computational and experimental studies on bis-1,2,4-triazinylpyridines (BTP, Figure a), , BTP-like compounds such as bis­(1,2,4-triazinyl)­bipyridines (BTBP, Figure b), as well as bis­(1,2,4-triazinyl)-1,10-phenanthrolines, and their derivatives. Computational studies of related ligands containing C, H, O, and N have also been reported, although experimental data are largely lacking for these systems. Experimental studies of BTP-related compounds report a wide range of separation factors (SFs) with variations in closely related systems over a factor of 10 4 , whereas in other systems the variations can range from 15 to 60 or from 4 to 50 .…”
Section: Introductionmentioning
confidence: 99%